Analisis Earned Value Pekerjaan Struktur Proyek Pembangunan Gedung XYZ - Hamonangan Girsang; Wasi Dwi Prastomo; Rangga Nelson Kurniawan (Universitas Mercu Buana, 2022)
AbstractProject implementation is sometimes dificult with various complex problems such as not being able to be completed as planned. not on time, quality, and costs which sometimes happen to be over budget. To overcome this, it is necessary to implement good cost, quality and time management. This study aims to determine the estimated costs and time required to complete a project as well as positive and negative performance factors.The research method in this paper is quantitative research with literature study. The data were collected through observation and discussion activities in the construction project of the XYZ Apartment Building in Bandung specifically on the structure section and the data were analyzed descriptively.From the Earned Value analysis, the research results show that the estimated cost required for the XYZ Bandung apartment development project until completion of all work is Rp. 169,118,439,088, - from the original planned budget of Rp. 164,552,000,000, - and the estimated total time required is 443 days from the originally planned schedule of 336 days. And as much as 29.1% (twenty nine point one percent) of the total work time of this project took place with a negative performance where the value of the resulting work package was lower than the costs that had been incurred and the packages that were carried out were less than the scheduled schedule. It is planned that due to several things such as the slow process of approval for image changes, the arrival of material that is not on time and decreased worker productivity due to the Covid pandemic and 70.9% of the total time for the project that has been underway is performing positively or well. Keywords: Analysis, Earned, Building, Project, Value.Abstrak Pelaksanaan proyek terkadang dihadapkan dengan berbagai masalah yang kompleks seperti tidak bisa diselesaikan sesuai dengan yang direncanakan. tidak tepat waktu, mutu, dan biayanya yang terkadang terjadi over budget Untuk mengatasi hal ini perlu adanya penerapan manajemen biaya, kualitas, dan waktu yang baik. Penelitian ini bertujuan mengetahui prakiraan biaya dan waktu yang diperlukan menyelesaikan sebuah proyek serta faktor-faktor kinerja positif dan negatif.Metoda penelitian dalam karya tulis ini yaitu penelitian kuantitatif dengan studi kepustakaan. Data dikumpulkan melalui kegiatan pengamatan dan diskusi di proyek pembangunan Gedung Apartemen XYZ di bandung secara khusus pada bagian struktur serta data tersebut dianalisis secara deskriptif.Dari analisa Earned Value hasil penelitian menunjukkan prakiraan biaya yang diperlukan pada proyek pembangunan apartemen XYZ Bandung sampai selesai semua pekerjaan adalah Rp. 169.118.439.088,- dari rencana anggaran semula sebesar Rp. 164.552.000.000,- dan prakiraan total waktu yang dibutuhkan adalah 443 hari dari jadwal yang direncakan semula 336 hari. Dan sebanyak 29,1% (dua puluh Sembilan koma satu persen) dari total waktu pengerjaan proyek ini berlangsung dengan kinerja negatif yang mana nilai paket pekerjaan yang dihasilkan dari lebih rendah dibandingkan dengan biaya yang sudah dikeluarkan dan paket paket yang terlaksana lebih sedikit dari jadwal yang direncanakan yang disebabkan beberapa hal seperti lambatnya proses approval perubahan gambar, kedatangan material yang tidak ontime dan produktifitas pekerja yang menurun akibat pandemic Covid dan sebesar 70,9% dari total waktu pelakasanaan proyek yang sudah berlangsung adalah berkinerja positif atau baik.